PELAKSANAAN PENDIDIKAN ISLAMI DI KOTA BANDA ACEH: Studi terhadap implementasi Qanun No. 5 Tahun 2008 - Cut Suraiya (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2015)
Qanun of education is hoped to be socialized in Aceh education. This research aims to give information and real description of islamic education in Banda Aceh city. The result showed that the concept of curriculum, educators, and educational institution in Qanun No. 5 year 2008 is the education run based on islamic values, foundations, and cultures as guidance to implement islamic law (syari’at) truly in every aspects of life. The implementation of curriculum, educators, and educational institution have contributed significantly, yet it still have to be improved.Overall, they are classified into good catagory. It showed that most of teachers have good impression toward the implementation of islamic education in Banda Aceh city.